Mathematical Model of The Spread of Foot and Mouth Diseases (FMD) - Hajar; Nacong, Nasria (JURNAL ILMIAH MATEMATIKA DAN TERAPAN, 2024)
Foot and Mouth Disease (FMD) is a contagious animal disease and can cause death. FMD is caused by an RNA virus belonging to the genus Apthovirus, family Picornaviridae. FMD can be transmitted through direct contact with exposed animals, indirect contact and through the air. In this research, a mathematical model of the spread of FMD in animal populations will be constructed by adapting the SIR (Susceptible, Infected, Recovered) model. From this model two critical points are obtained. The first critical point is the disease-free critical point and the second critical point is the endemic critical point for FMD. The existence of can be guaranteed, because all parameters are positive. And it is stable jika .. Furthermore exists and is stable if ..